Energy loss for heavy ions in polymers: A possible correlation with the induced changes in optical and electrical properties. Issue 1 (17th February 2015) - Sharma, Kalpana; Neetu,; Kumar, Vijay; Pal, Rishi; Kumar, Shyam
Abstract: Polymers are being widely used as versatile materials in many scientific and technological applications because of their excellent inherent characteristics along with the possibility to further improve their properties through various treatments like chemical doping, gamma irradiation, ion beam irradiation etc. There are many reports in the literature where the optical, mechanical and electrical properties of the polymers are improved after irradiation to ion beams. Such changes are as a result of the energy transferred by the incident ion leading to the structural changes in the polymers. For the quantitative data interpretation in such experiments it is highly essential to know the exact values of energy deposited by the incident ion in the polymeric material. In the present work, a new approach without any empirical parameterizations for the correct evaluation of energy transfer by the incident ion beam within the polymeric material has been developed. Finally, the observed changes in the optical and electrical properties of PET polymer, as quoted in the literature, have been tried to be explained in terms of the energy transferred by the incident ions.